PENGUATAN SIKAP MODERASI SISWA DALAM PEMBELAJARAN AGAMA ISLAM DI SMP MAMBAUS SHOLIHIN TUBAN - Saeful Anam; Siti Faridatul Afifah (JURNAL ILMIAH NUSANTARA, 2025)
The role of the younger generation as agents of change is crucial in addressing identity search and potential extremism among adolescents. Therefore, strengthening moderate attitudes among students is essential for them to understand moderation, especially in the modern era. This study aims to answer two questions: 1) how to strengthen students' moderate attitudes through Islamic religious education, and 2) how this is implemented in schools. This qualitative research employs a phenomenological approach at Mambaus Sholihin Junior High School in Tuban, utilizing data collection methods such as interviews, observations, and documentation. The findings indicate that strengthening moderate attitudes is achieved through comprehensive religious education, leadership training, social activities, teacher role modeling, wise use of technology, and parental involvement. Religious moderation also encompasses the development of attitudes and behaviors that reflect balanced and inclusive Islamic teachings.